Effect of La2Zr2O7 coat on the hot corrosion of multi-layer thermal barrier coatings. (15th July 2016) - Naga, S.M.; Awaad, M.; El-Maghraby, H.F.; Hassan, A.M.; Elhoriny, M.; Killinger, A.; Gadow, R.
Abstract: In the present study, a multi-layer thermal barrier coating (TBC) consisting of ZrO2 and La2 Zr2 O7 layers was designed in order to study the effect of the sequential layering and the composition of the top layer on hot corrosion resistance against a (1:1) V2 O5 /Na2 SO4 mixture. Accordingly, functionally graded YSZ/La2 Zr2 O7 thermal barrier coatings (TBCs) were deposited on the surface of a stainless steel 1.4301 alloy using the plasma spray technique. Lanthanum zirconate powder was synthesized via the sol–gel method. The cross-sectional morphologies, phase constitution, microstructure, and hot corrosion resistance of the multi-layered coatings were studied. X-ray diffraction and scanning electron microscope results revealed an improvement in the corrosion resistance, at 900 °C for 50 h, of samples with YSZ over those with only YSZ and La2 Zr2 O7 top coats. Graphical abstract: Highlights: TBC of Al2 O3 /La2 Zr2 O7 /YSZ coat were deposited on the surface of 1.4301 alloy by plasma spraying. Pure nano-size La2 Zr2 O7 phase was prepared using the sol–gel technique. Hot corrosion behavior of the coat sample was investigated. Two different corrosion products are observed in the hot treated samples.